2012
DOI: 10.14742/ajet.844
|View full text |Cite
|
Sign up to set email alerts
|

In search of a method to assess dispositional behaviours: The case of Otago Virtual Hospital

Abstract: <span>While the potentials of virtual worlds to support experiential learning in medical education are well documented, assessment of student learning within these environments is relatively scarce and often incongruent. In this article, a conceptual framework is proposed for formatively assessing dispositional behaviours in scenario-based learning within a virtual world. The framework was devised for use with medical students playing the roles of junior doctors as they solve open-ended clinical cases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Of the included studies, most studies were either randomized controlled trials (RCTs; 47/114, 41.2%) or other experimental design studies (eg, before-and-after and cross-over studies; 49/114, 42.9%). Of the 114 studies, 14 (12.3%) were cross-sectional studies [ 35 - 49 ], 3 (2.6%) were case series or case studies [ 42 , 50 , 51 ], and 1 (0.9%) was a meta-analysis that examined the effectiveness of 3D anatomical models in teaching anatomy [ 52 ], which found that 3D anatomical models yielded significantly better results for user satisfaction and perceived effectiveness compared with conventional 2D teaching methods. An overview of the study characteristics is provided in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the included studies, most studies were either randomized controlled trials (RCTs; 47/114, 41.2%) or other experimental design studies (eg, before-and-after and cross-over studies; 49/114, 42.9%). Of the 114 studies, 14 (12.3%) were cross-sectional studies [ 35 - 49 ], 3 (2.6%) were case series or case studies [ 42 , 50 , 51 ], and 1 (0.9%) was a meta-analysis that examined the effectiveness of 3D anatomical models in teaching anatomy [ 52 ], which found that 3D anatomical models yielded significantly better results for user satisfaction and perceived effectiveness compared with conventional 2D teaching methods. An overview of the study characteristics is provided in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 114 papers, 69 (60.5%) concerned surgical VR simulators [ 36 , 37 , 42 , 46 , 47 , 51 , 53 , 55 - 57 , 59 , 66 , 67 , 73 - 75 , 79 , 81 - 84 , 86 , 88 , 90 - 94 , 96 , 98 - 100 , 103 , 105 , 107 - 138 ], 20 (17.5%) used virtual worlds or virtual environments [ 39 - 41 , 43 , 44 , 48 , 50 , 58 , 69 , 70 , 76 - 78 , 101 , 139 - 145 ], 15 (13.2%) used 3D anatomical models, 4 (3.5%) used virtual dissection tables [ 9 , 62 , 97 , 127 , 146 ], 4 (3.5%) used mobile VR [ 14 , 63 , 65 , 147 ], 1 (0.9%) examined the use of a virtual palpation simulator, and 1 (0.9%) used a virtual ultrasound simulator ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expectations for simulations are high in healthcare education; their use is expected to improve patient care and enhance patient safety. In healthcare education, simulations are expected to improve learning and provide students with experiential learning opportunities (Cleave-Hogg & Morgan, 2002;Gaba, 2004;Loke, Blyth & Swan, 2012;Rall & Dieckmann, 2005). Simulations potentially provide a safe and realistic learning environment in which repeated practice is possible.…”
Section: Introductionmentioning
confidence: 99%